Site-Directed Mutagenesis in Viral Glycoprotein and Its Role in Viral Diagnostics and Therapy - Jawa, Basem (Journal of King Abdulaziz University: Medical Sciences, 2024)
Site-directed mutagenesis introduces precise mutations into viral glycoprotein genes, allowing the study of their structural and functional roles and interactions with host cells. By modifying specific amino acids, researchers can assess the impact on viral entry, replication, and immune evasion. Engineered glycoproteins improve diagnostic assays sensitivity and specificity and facilitate the development of better vaccine antigens. Therapeutically, site-directed mutagenesis aids in designing antiviral drugs targeting specific glycoprotein regions and developing attenuated viral strains for vaccines. Additionally, this approach enhances understanding of viral evolution and adaptation, offering insights into future pandemic threats and aiding preparedness efforts.